ANALISA PENAMBAHAN VORTEX GENERATOR PADA KARAKTERISTIK AERODINAMIKA PADA DESAIN MOBIL CYBERTRUCK DENGAN METODE SIMULASI CFD - Fahri, Fahri; Arifin, Fatahul; Martomi, Eka Satria (MACHINERY Jurnal Teknologi Terapan, 2024)
This study purpose to determine the effect of the Vortex Generator on the design of Cybertruck with variations in the fillet radius on the vortex side, namely 10 °, 20 ° and 30 °. The variations location of vortex generator speeds on 80 Km/h and 100 Km/h, The CFD analysis is simulated by ansys. The comparison results, were found that the Vortex Generator on the car model with a 20 ° fillet radius design placed at the front has an influence on reducing the drag coefficient, namely reducing the drag coefficient and force drag on the cybertruck with a cd of 0.45266866 and Fd of 481.77061 N at a speed of 80 Km/h then cd of 0.45201879 and Fd of 748.97953 N at a speed of 100 Km/h, That means the vortex generator was very influential in reducing CD and Fd on Cybertruck.